TIKTOK SEBAGAI MEDIA PERSONAL BRANDING MELINDA ROHITA - Farid Ardiansyah; Kukuh Sinduwiatmo (Universitas Prof. Dr. Moestopo (Beragama), 2023)
One of the communication strategies that instills a person's positive perception to the public is to do a personal branding. The presence of TikTok has the function of being able to make a digital marketing strategy and build a brand, with TikTok being able to influence the behavior of its followers. One of them is the TikTok celebrity Melinda Rohita, also known as Meyden, who is famous because her personality is considered fun and entertaining. This research method used is descriptive qualitative by focusing on research case studies, namely knowing the form of Melinda Rohita's personal branding through her Tiktok social media account @imeyhou. Supported by eight main concepts of Peter Montoya's personal branding. The results of her research show that Melinda Rohita's personal branding fulfills the eight main concepts, namely specialization, leadership, personality, difference, visibility, unity, firmness and good name. With a distinctive and strong character in forming personal branding as a smart, fun, and entertaining teenager. Not only that, by using the TikTok application which has completed various special features with various decorations when making videos, then uploading them to the TikTok media account. So that the @imeyhou account utilizes three supporting elements provided by TikTok, namely: live TikTok, TikTok shop, and popular.